Innovative Model for Developing the Service System in the Agro-Industrial Complex Based on Clustering Principles - Ruziev Xamrokul; Shukurova Marhabo; Feruza Usarqulova (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The agro-industrial complex serves as a cornerstone of national economic stability, integrating agricultural production, processing, and distribution systems that ensure food security and rural development. Specific Background: Rapid globalization, technological change, and increasing competitiveness have revealed the inefficiency of conventional service infrastructures in agro-industrial systems, particularly in resource utilization, innovation adoption, and coordination among stakeholders. Knowledge Gap: Despite the global emphasis on clustering as a driver of competitiveness, there remains limited empirical and methodological understanding of how cluster-based service models can optimize performance through digital and economic integration in emerging economies such as Uzbekistan. Aims: This study aims to develop an innovative cluster-based model for agro-industrial service systems that enhances efficiency, technological independence, and competitiveness through mathematical modeling and digital monitoring tools. Results: The proposed model integrates key indicators—including technical independence, infrastructure competitiveness, socio-economic stability, and export potential—into a unified efficiency index supported by regression-based analysis. The findings demonstrate that implementing a Public-Private Partnership (PPP)-driven cluster framework enables balanced investment distribution, improved financial flow management, and enhanced innovation performance across the agro-industrial value chain. Novelty: The study introduces a digitally enabled cluster model governed by Key Performance Indicators (KPIs) and data analytics, providing a new paradigm for evaluating and optimizing service systems in agro-industrial networks. Implications: The model offers a replicable framework for policymakers and practitioners to foster sustainable agro-industrial development, enhance investment attractiveness, and strengthen economic resilience in developing regions. Highlights: Introduces a cluster-based digital model to enhance agro-industrial efficiency. Develops a unified efficiency index integrating key economic and technical indicators. Promotes PPP-driven collaboration for sustainable and competitive agro-industrial growth. Keywords: Agro-industrial Cluster, Innovation, Competitiveness, Digital Model, Sustainability